The theoretical and practical implications of Criminal Convention regarding the corruption concluded in Strasbourg 1999 upon Romanian legislation - Sabău-Pop, Olimpiu Aurelian (Debreceni Jogi Műhely, 2011)
Considering Resolution (58)7 regarding the authorisation of creating of an enlarged partial Agreement, which establishes the Group of States against corruption - GRECO, the Penal Convention regarding Corruption was also issued in January 27, 1999 at Strasbourg (STEN 173), convention which had a decisive impact upon changing the vision of the Romanian legislator regarding aspects concerning the notion of ‘corruption’, both of incriminatory as well as of procedural order.